Pengenalan Uang Layak Edar Dan Tidak Layak Edar Kepada Anak - Anak Di Lingkungan Desa Cibatu Purwakarta - Jalaludin, Jalaludin; Saldianasari, Rina; Apriani, Riska; Sari, Natasya Wulan (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Based on the observations of the PKM team, they found several phenomena related to money worthy of circulation and not worthy of circulation in Cibatu Village, one of which is that there are still few parties who care about money worthy of circulation and not circulating to children and the people of Cibatu Purwakarta Village. The second phenomenon is that children who often write on banknotes, either with romantic words or just scribbling numbers or lines, do not know that such actions are categorized as damaging money. The third phenomenon is the limited understanding of the children and the community about money worthy of circulation and not worthy of circulation, damaged and undamaged money. So the purpose of this PKM is to conduct Educational PKM: socialization of money worthy of circulation and not worthy of circulation to children in the Cibatu Purwakarta Village environment. This PKM method uses socialization and discussion. The results of PKM on the socialization of money worthy of circulation and not worthy of circulation to children in the Cibatu Purwakarta village environment get satisfactory results, because the average result of understanding the children of Cibatu Village on money worthy of circulation and not worthy of circulation is 80.19%. Through this PKM activity, it is hoped that it can form a smart, responsible, and caring young generation for the environment, including in terms of money management. Thus, children can contribute positively to the development of Cibatu Purwakarta village.